The Routledge anthology of women's theatre theory and dramatic criticism - Burroughs, Catherine B., 1958-; Gainor, J. Ellen (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"The Routledge Anthology of Women's Theatre Theory and Dramatic Criticism is the first wide-ranging anthology of theatre theory and dramatic criticism by women writers. Reproducing key primary documents contextualized by short essays, the collection situates women's writing within, and also reframes the field's male-defined and male-dominated traditions. Its collection of documents demonstrates women's consistent and wide-ranging engagement with writing about theatre and performance and offers a more expansive understanding of the forms and locations of such theoretical and critical writing, dealing with performances that often lay outside established publication venues. This alternative tradition of theatre writing that emerges allow contemporary readers to form new ways of conceptualizing the field, bringing to the fore a long-neglected, vibrant, intelligent, deeply informed, and expanded canon that generates a new era of scholarship, learning, and artistry. The Routledge Anthology of Women's Theatrical Theory and Dramatic Criticism is an important intervention into the fields of Theatre & Performance Studies, Literary Studies, and Cultural History, while adding new dimensions to Feminist, Gender & Sexuality Studies"--
Keywords: Dramatic criticism; Women theater critics; Feminist criticism; PERFORMING ARTS / Theater / History & Criticism